Training on Making "Complete Feed" for Goat Feed in Wanagiri Village, Sukasada SubSubdistrict, Buleleng Regency - Luh Suariani; Sharil Fadli Mohamad Zamri; I Nyoman Kaca; Made Yudiastari; Yan Tonga; Ni Ketut Etty Suwitari; Ni Ketut Mardewi; I Gusti Agus Maha Putra Sanjaya; Ni Made Ayu Gemuh Rasa Astiti; Made Adi Wiratama; Agung Pamuji; I Made Deddy Dharmika; Ni Luh Adelia Dharma Prakerti; I Wayan Eka Ariawan (Asian Journal of Community Services, 2023)
Wanagiri Village is a village located in Sukasada SubSubdistrict, Buleleng Regency. Most of the people's livelihoods are farmers, ranchers, and coffee processors, which have the potential to be developed. From the main output of coffee, a complete feed will be made that utilizes coffee waste as feed for the PE goats that are widely raised there. In addition, the partners lacked knowledge in the field of feed, especially utilizing coffee waste as feed by mixing it with superior forage available there, both grass and legumes. Therefore, the right ratio formulation technique can be given to FE goats. Solutions made to solve problems faced by partners in making complete feed for goats. The method that will be used is the farmer's active participation extension method and explorative.